PENDIDIKAN BERKUALITAS: MENCIPTAKAN HUBUNGAN PERTEMANAN YANG SEHAT DI KALANGAN SISWA DALAM MENGURANGI BULLYING DI LINGKUNGAN SEKOLAH - Riri Herawati Prasojo; Uswatun Hasanah; Maya Oktaviani (Prosiding Temu Ilmiah Nasional Guru, 2024)
To improve the quality of Human Resources, it is necessary to improve the quality of education. In this case, the quality of education in Indonesia is expected to be able to bring progress to a nation and state. To overcome this, the Sustainable Development Goals (SDGs) program was enacted. One of the indicators of the implementation of the 4th SDGs is "ensuring equal, inclusive quality education and supporting lifelong learning opportunities for all". The purpose of this study is to find out the involvement of healthy friendship relationships among students in reducing bullying in the school environment. This research method uses an associative quantitative approach. This research was carried out in State Junior High Schools in DKI Jakarta, with a population of 1,620 and a sample of 324 State Junior High School students in DKI Jakarta. The results of this study showed that peer relationships had a significant relationship with bullying (P value = 0.000<0.05). The correlation coefficient is -0.253 which means that the two variables have a negative relationship with a weak level of closeness. In this case, healthy friendships can reduce bullying in the school environment